Assessing the morphological and physiological adaptations of the parasitoid wasp Echthrodesis lamorali for survival in an intertidal environment. (22nd February 2017) - Owen, Candice A.; Coetzee, Julie A.; van Noort, Simon; Austin, Andrew D.
Abstract: As a result of a variety of chemical, environmental, mechanical and physiological difficulties, insects that spend their entire life spans in the marine or intertidal region are relatively rare. The present study assesses whether morphological and physiological adaptations have evolved in a maritime parasitoid wasp species Echthrodesis lamorali Masner, 1968 (Hymenoptera: Platygastridae, Scelioninae), in response to environmental pressures on its respiratory functioning. Scanning electron and light microscopy of whole and sectioned specimens show the presence of structure‐retaining taenidia in the tracheal tubes, although there is an absence of other major adaptations associated with the trachea or spiracles. Histological sectioning reveals the presence of unusual sacs in the female metasoma whose role is unknown, although they are hypothesized to most likely be linked to ovipositor control. Respirometry experiments illustrate the formation of a plastron when submerged, with the longevity of the wasps being increased by quiescence. The critical thermal range of E. lamorali is shown to be large: from −1.1 °C ± 0.16 to 45.7 °C ± 0.26 (mean ± SE). Behavioural and physiological adaptations in E. lamorali appear to have evolved in response to exposure to the heterogeneous environmental conditions experienced within the intertidal zone.